(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the role and importance of technological science in the educational system, the training of competitive specialists in various fields in the continuous education system of our Republic, the creation of conditions for their acquisition of high knowledge, skills and qualifications, the activities of highly qualified specialists in the production process Information is given that the organization of technology (labor education) science process is of great importance in fulfilling the social order set by the organization.